Between English and Mandarin: A Contrastive Study of Interrogative Sentences among Indonesian Textbooks - Emy Damayanti; Syifa Khuriyatuz Zahro (Prodi Pendidikan Bahasa Inggris, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Islam Darul Ulum Lamongan*, 2022)
Indonesian students in senior high school in the language program found it difficult to make both English interrogative sentences and Mandarin interrogative sentences. To assist the English and Mandarin teachers in overcoming the problem, a contrastive study of both English and Mandarin interrogative sentences needs to be investigated. Hence, this article purposes to reveal the similarities and differences between English and Mandarin interrogative sentences found in Indonesian textbooks used by teachers. Qualitative descriptive research was used by describing both similarities and differences. The result generates several similarities and differences in interrogative sentences between English and Mandarin. Both languages are similar because they both have five kinds of interrogative sentences which have the same meaning and required similar answers. Among five types of interrogative sentences in English or Mandarin, some of them use several predicates and object simultaneously in one question. The use of the auxiliary verb in English and Mandarine's interrogative sentence is dissimilar. In English interrogative sentences, auxiliary verbs are used accord with the tenses used, while in Mandarin they are not. Besides, auxiliary verbs in English interrogative sentences must precede the subject, but in Mandarin, they are at the end of the sentence.